An Analysis of Figurative Language in Song Lyrics of Jason Mraz in Album Mystical Magical Rhythmical Radical Ride: English - Abdul Aziz; Firqo Amelia; Yopi Thahara (JOEY: Journal of English Ibrahimy, 2025)
Lyrics and music have always been essential components of art, and their actual meaning can be discovered in the way sounds are arranged over time. The songs' deeper meanings and implications, however, may not be fully understood by many listeners. This thesis investigated the deeper meanings conveyed by figurative language in Jason Mraz's album Mystical Magical Rhythmical Radical Ride. The idea was to demonstrate that, in addition to simply appreciating the music, listeners may discover topics like love and life's journey. The songs gained depth and a personal touch from the use of figurative language, which uses literary devices to suggest meanings beyond the literal. In order to determine which figurative language forms were most prevalent in Mraz's lyrics, this study identified a variety of them. A qualitative method was applied, Classifying the data according to Perrine's (1977) theory, analyzing the data, going over the lyrics and their interpretations, and making conclusions are the four processes that follow. Numerous figurative language types, including similes, metaphors, hyperbole, personification, metonymy, understatement, and irony, were found in the songs, with metaphors being the most prevalent. These symbolic components expressed several ideas: Social, Connotative, and Conceptual